Morphometric variation in Clethrionomys gapperi : are all voles created equal? - Mihok, Steve; Fuller, William A. (Canadian Journal of Zoology, 1981)
A general feature of population cycles in microtine rodents is the Chitty effect: large body size in peak populations. This phenomenon does not occur in a subarctic population of Clethrionomys gapperi that has been studied extensively for 15 years. Voles from various phases of the population cycle differ primarily in terms of complex patterns of "shape" rather than "size." These patterns are strongly correlated with environmental conditions during periods of growth or thermal stress. Increasing populations are nevertheless characterized by changes in the relationships between body size and skull size. Voles larger than predicted on the basis of their skull size are captured in springs characterized by an increase in density from the previous spring. Hence the Chitty effect is present in this population but it is expressed in a different way. Qualitative changes in some weakly cycling microtine populations may therefore be relatively difficult to detect without a better understanding of the mechanisms underlying this morphometric, behavioural, genetic complex.